Peran Ekonomi Biru Dalam Memperkuat Ketahanan Ekonomi : Studi Kasus Kawasan Wisata Mangrove di Surabaya - Virna Febryaningrum; Sindi Mayangsari; Maria Yovita R. Pandin (Universitas Kristen Indonesia Toraja, 2024)
This article aims to investigate the role of the blue economy in strengthening economic resilience with a focus on its contribution to increasing economic diversification, food security, job creation, environmental sustainability, and resilience to climate change. This research uses a descriptive analytical approach by collecting and analyzing information from various primary and secondary sources, including scientific literature, research reports, and statistical data related to the blue economy and economic resilience. The blue economy has a significant role in strengthening economic resilience in several ways. First, the blue economy opens up new opportunities for economic diversification, especially for countries that depend on traditional sectors such as agriculture and mining. Furthermore, through the development of sustainable fish farming and marine agriculture, the blue economy can help improve food security